Simulation of production processes with Plant Simulation - Miltényi, Máté; Czégé, Levente (International Journal of Engineering and Management Sciences, 2019)
This article presents the modelling of interconnected companies’ logistic processes with Tecnomatix Plant Simulation by Siemens. It has two main parts. The first contains the details of recognition including simulation. The second part presents the modelling with Tecnomatix Plant Simulation. My publication is supported by the EFOP3.6.1-16-2016-00022 project. The project is co-financed by the European Union and the European Social Fund.